Association between socioeconomic status and joint replacement of the hip and knee: a population‐based cohort study of older adults in Tasmania. Issue 2 (20th February 2022) - Munugoda, Ishanka P.; Brennan‐Olsen, Sharon L.; Wills, Karen; Cai, Guoqi; Graves, Stephen E.; Lorimer, Michelle; Cicuttini, Flavia M.; Callisaya, Michele L.; Aitken, Dawn; Jones, Graeme
Abstract: Background: A socioeconomic gradient exists in the utilisation of total hip replacements (THR) and total knee replacements (TKR) for osteoarthritis. However, the relations between socioeconomic status (SES) and time to THR or TKR is unknown. Aim: To describe the association between SES and time to THR and TKR. Methods: One thousand and seventy‐two older adults residing in Tasmania, Australia, were studied. Incident primary THR and TKR were determined by data linkage to the Australian Orthopaedic Association National Joint Replacement Registry. At baseline, each participant's area‐level SES was determined using the Index of Relative Socioeconomic Advantage and Disadvantage (IRSAD) from the Australian Bureau of Statistics' 2001 census data. The IRSAD was analysed in two ways: (i) categorised into quartiles, whereby quartile 1 represented the most socioeconomically disadvantaged group; and (ii) the cohort dichotomised at the quartile 1 cut‐point. Results: The mean age was 63.0 (±7.5) years and 51% were women. Over the median follow up of 12.9 (interquartile range: 12.2–13.9) years, 56 (5%) participants had a THR and 79 (7%) had a TKR. Compared with the most disadvantaged quartile, less disadvantaged participants were less likely to have a THR (i.e. less disadvantaged participants had a longer time to THR; hazard ratio (HR): 0.56; 95% confidence interval (CI) 0.32, 1.00) but not TKR (HR: 0.90; 95% CI 0.53, 1.54). However, the former became non‐significant after adjustment for pain and radiographic osteoarthritis, suggesting that the associations may be mediated by these factors. Conclusions: The present study suggests that time to joint replacement was determined according to the symptoms/need of the participants rather than their SES.